Iran's intellectual revolution - Kamrava, Mehran (Cambridge University, 2013)
Since its revolution in 1979, Iran has been viewed as the bastion of radical Islam and a sponsor of terrorism. The focus on its volatile internal politics and its foreign relations has, according to Kamrava, distracted attention from more subtle transformations which have been taking place there in the intervening years. With the death of Ayatollah Khomeini a more relaxed political environment opened up in Iran